An analytical study of the reality and prospects of using blockchain technology in the commercial and takaful insurance industry - بونعجة سحنون (Université de M'sila, 2021)
This study aimed at identifying blockchain technology and analyzing the reality of its use by commercial insurance companies, and it has been shown that there is a trend by many of these companies in their reliance on this technology through the use of startups, where they succeeded in introducing innovative insurance products, based on blockchain technology, such as smart contracts, peer-to-peer insurance, as insurance companies seek to first achieve their experiences in blockchain technology. The study also concluded that in the near future blockchain will change the entire profile of the insurance industry, with benefits and opportunities that are not currently available.
Keywords: blockchain, insurance industry, solidarity insurance, smart contracts. Jel Classification Codes : O310, O350, O360